A mixed-function-grafted magnetic mesoporous hollow silica microsphere immobilized lipase strategy for ultrafast transesterification in a solvent-free system1. Issue 54 (13th June 2015) - Zheng, Mingming; Mao, Lijing; Huang, Fenghong; Xiang, Xia; Deng, Qianchun; Feng, Yuqi
<x xml:space="preserve">Abstract</x> A novel magnetic mesoporous hollow silica microspheres immobilized lipase is described for ultrafast transesterification of phytosterol with fatty acids and triglycerides in a solvent-free system.